2018
DOI: 10.1080/10503307.2018.1489162
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy for eating disorders: A meta-analysis of direct comparisons

Abstract: Generally, the results indicate that any bona fide psychotherapy will be equally effective. While the number of trials remains modest, we hope that as more research becomes available, treatment guidelines can be updated, and more evidence-based treatment options will be available for treating EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 37 publications
1
28
0
4
Order By: Relevance
“…For the latter purpose, offering shared decision‐making and creating supportive environments may be particularly effective. The application of evidence‐based treatments for these disorders is a critical area that needs to be pursued, but therapeutic alliance has been identified as a non‐specific therapeutic factor that significantly contributes to promoting recovery.…”
mentioning
confidence: 99%
“…For the latter purpose, offering shared decision‐making and creating supportive environments may be particularly effective. The application of evidence‐based treatments for these disorders is a critical area that needs to be pursued, but therapeutic alliance has been identified as a non‐specific therapeutic factor that significantly contributes to promoting recovery.…”
mentioning
confidence: 99%
“…Treatment trials of adults with anorexia nervosa include a substantial proportion with a prolonged period of untreated illness. It could be argued that the findings from these studies have led to “therapeutic stagnation.” For example, no superiority of a specific psychological approach has been observed for adults with anorexia nervosa (Grenon et al, ; Zeeck et al, ). In addition, all produce only moderate sized effects.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic literature search of electronic databases (PsycINFO, MEDLINE, Cochrane Central Register of Controlled Trials, http://clinicaltrials.gov) was conducted separately for group and individual psychotherapy RCTs for adults with an ED. Full methodology is provided in two previous meta‐analyses (Grenon et al, ; Grenon et al, in press).…”
Section: Methodsmentioning
confidence: 99%
“…Two recent meta‐analyses (Grenon et al, ; Grenon et al, in press) of RCTs demonstrated that psychotherapy for EDs is effective. Despite this, it is possible that the magnitude of the effects of psychotherapies for EDs may be biased by the methodological quality of the included RCTs (Moher et al, ; Schulz et al, ; Higgins et al, ).…”
Section: Introductionmentioning
confidence: 99%